Cross-sectional study: knowledge and practice of proper disposal of medication among patients in Hospital Sultanah Bahiyah (HSB), Alor Setar - Zainol, Nor Azween; Syed Mansor, Syed Muhamad Nor Iman; Mohamad Noor, Mohamad Nabil Nazmi (2017)
Medication plays an important role in treating disease, but when they are no longer needed it is crucial to dispose them properly for the safety of public and environment. Therefore, knowledge and practice of correct way to dispose medication are essential to community . Lack of knowledge and practice may affect the ecosystem especially to environment, which need to be preserved and cared about . The aim of the study was to assess the knowledge , practice and factor contributing to proper disposal of medication among patient in Hospital Sultanah Bahiyah, Alor Setar. This study was conducted among 200 patients who were randomly selected using convenient sampling in Hospital Sultanah Bahiyah (HSB) from December 2016 to February 2017 by using self-administered questionnaires. The questionnaire was divided into four parts, which consist of demographic factor, prevalence of proper disposal of medication, practice of proper disposal of medication, and knowledge about medication disposal. The data were analysed by SPSS version 22.0 software. The finding shows 160 (80%) of participants have unused or leftover medication, where majority (26.6%) of the respondents were having their medication from the prior illness. Analgesics or painkillers (45.2%) were the most common medicines stored at home. The popular ways of disposing medicines were throwing them into the garbage with 44% and 10.5% chose toilet or sink as a method of disposing. However, 18.6% of them chose to return remaining drugs to pharmacy. There were (14%) of the respondents who still think that improper disposal of medication exact no effect towards the environment and ecosystem, and whole (28%) respondents stated that burning method is an environmentally sound way of medication disposal. Most of the patients are lacking of information and have low knowledge about proper medication disposal. Majority of the patients were practicing wrong way of disposing medicines, which may cause many problems in the future. However , most of respondents were aware that drug abusing may occur and as well as affecting environment. This survey suggested that there is an urgent need to develop awareness on knowledge and public disposing policies in order to reduce pharmaceutical wastage and environmentally pollution.